The business imperative: Helping small family farmers to move up or move out - Fan, Shenggen; Brzeska, Joanna; Olofinbiyi, Tolulope (International Food Policy Research Institute, 2015)
How can family farmers best contribute to their country’s agriculture needs as well as broader development goals? First, we should determine which farmers can be profitable and assist them in doing so. Second, for those who aren’t profitable, we need to help them shift to other economic pursuits.